Insurance coverage does not predict outcomes of genetic testing: The search for meaning in payer decisions for germline cancer tests. Issue 6 (17th July 2019) - Amendola, Laura M.; Hart, M. Ragan; Bennett, Robin L.; Horike‐Pyne, Martha; Dorschner, Michael; Shirts, Brian; Jarvik, Gail P.
Abstract: In this work, we explore the results of germline cancer genetic tests in individuals whose insurance would not cover this testing. We enrolled 31 patients with a personal history of cancer whose health insurer denied coverage for a clinical germline cancer panel genetic test recommended by a medical genetics provider into a study providing exome sequencing and return of cancer‐related results. Five participants (16%) had a pathogenic variant identified related to increased cancer risk. Three participants (10%) had a variant of uncertain significance (VUS) in a gene related to their cancer history. These rates are not significantly different than the 12% rate of pathogenic or likely pathogenic (P/LP) variants and VUS in 1, 462 patients approved by insurance to have a similar clinical germline cancer test ( p = .59 for P/LP variants; p = .87 for VUS; Shirts et al., Genet Med, 18:974, 2016). Health insurance guidelines may not meaningfully differentiate between patients with cancer who are likely to benefit from germline cancer genetic testing and those who will not. Failure to identify pathogenic variants in this research cohort would have led to suboptimal care. Strategic evaluation of current germline cancer genetic testing coverage policies is needed to appropriately deliver precision medicine.